Infuence of pH on the thermal inactivation kinetics of horseradish peroxidase in aqueous solution - Lemos, Maria Adília (2011)
The thermal inactivation of horseradish peroxidase in aqueous solution was studied in the pH range of 3.0 to 12.5, at temperatures ranging from 40 3C to 95 3C. The data were well xtted by a double exponential model. The enzyme showed highest stability around neutral pH and the stability was particularly decreased above pH 11. The z value of the less labile fraction at pH 11.5 to 12.5 (temperatures from 40 to 65 3C) and of the more labile fraction at pH 3}4 (temperatures from 65 to 85 3C) were close to 10 3C, making these systems suitable as time-temperature integrators for assessing microbial lethality in thermal processing of low-acid foods, particularly if they can be stabilized further without awecting their low z-value.